Cocaine trafficking in Latin America : EU and US policy responses - Fukumi, Sayaka, 1973- (Global security in a changing world., 2008)
The European Union and the United States have identified Latin American cocaine trafficking as a security threat, but their policy responses to it have differed. This book examines the ways in which the EU and the US have conceptualized this threat.